The Impact of Broadband Internet on Employment in France - Georges V. Houngbonon; Julienne Liang (International Telecommunications Society (ITS), 2018)
The impact of broadband Internet on employment is ambiguous, but empirical evidence is still limited. In this paper, we exploit data on a massive adoption of broadband Internet in France to investigate the impact of broadband Internet on employment. Using a fuzzy difference-in-difference estimation strategy, we find that broadband Internet destroy jobs, although the unemployment rate seems not to be affected. This job destruction occurs in manufacturing activities, contrary to the service sector where broadband Internet adoption creates jobs. In addition, we find that raising the level of education in urban areas tends to alleviate the negative impact of broadband Internet on employment.
Keywords: D31; L96; O15; 330; Broadband Internet; Employment